Assessment of Arsenic Content in Deep Groundwater of Kathmandu Valley, Nepal - Gwachha, Sushila; Acharya, Bishwa Nath; Dhakal, Agni; Shrestha, Sujen Man; Joshi, Tista Prasai (Nepal Journal of Science and Technology, 2020)
The contamination of groundwater by arsenic is one of the major problems in Nepal. This study was conducted in 20 deep groundwater (>200 m) samples of Kathmandu valley to assess the arsenic content of different groundwater zones and to determine the relationship of arsenic with physico-chemical parameters. Samples were collected in the post-monsoon season of 2016. The random sampling method was applied for the collection of water samples. Standard methods as APHA 2005 was followed for the analysis of the water sample. Arsenic concentration showed spatial variation. The maximum concentration of arsenic was found in Central Groundwater Zone at Patan (27040’07.3” and 85019’14”). Karl Pearson’s correlation coefficient revealed that moderate positive correlation of arsenic concentration with electrical conductivity (μS/cm) (r = 0.58 and p =0.01) and turbidity (NTU) (r = 0.67 and p = 0.01). Groundwater consumers of the central zone of the valley are at risk of arsenic-based health issues.